The impact of location of fuel service stations on the performance of signalized intersections in Kumasi - Debrah, Kwasi Edmund (2015)
A thesis submitted to the department of civil engineering, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science in Civil and Geomatic Engineering, 2009